Komunikasi Sosial Capital Sebagai Dakwah Kultural pada Masyarakat Islam di Pelosok Desa - Supriyo Wira (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2021)
Indonesia needs to have social capital so that groups living in a society consisting of approximately 500 ethnic groups can unite. Every ethnicity has the potential to maintain its culture and territory. Moreover, Indonesia is a country where most of the population lives in rural areas and only a small part lives in urban areas. With the lack of economic development and education in the rural villages, the information flowing in the villages is not as fast and significant as in the cities. Even the da'i (preachers) have to fight harder to gain trust, so that they can provide precise and accurate religious information to the village community. This study discusses deeper on how Social Capital communication as a cultural da'wah can touch the community, especially in rural areas, to absorb religious information properly and correctly. This case study employs literature review method in collecting the data. The descriptive approach employed in this study also helps investigate the status of the existing factors and then looks at the relationship between one factor and another. Human resources or human capital is a very important and strategic capital in the life of a community organization. This is especially in terms of how a preacher as a communicator can convey his da'wah message to the village community, with a cultural and belief approach. Such way of communication is what makes the village communities easier to accept the da'wah activities since they are based on trust, mutual understanding and shared values. In addition, the communicators also convey all information about religion according to the existing culture and beliefs.